Influence of crop load on the yield and grape quality of Merlot and Vranac (Vitis vinifera L.) varieties in Trebinje vineyard - Mersija DELIĆ; Fikreta BEHMEN; Saša MATIJAŠEVIĆ; Šaćira MANDAL; Saud HAMIDOVIĆ; Senad MURTIĆ (Acta Agriculturae Slovenica, 2021)
The aim of this study was to study the impact of crop load on the yield and grape quality of ‘Merlot’ and ‘Vranac’ (Vitis vinifera L.) in Trebinje vineyard. The crop load levels studied in this trial were 9 buds (V1) and 12 buds (V2) per vine at each variety trained on Lenz-Moser bilateral cordon system. The impact was determined by measurements of yield per vine and grape quality characterized by the contents of total soluble solids, titratable acidity, total phenolics, total flavonoids and by total antioxidant capacity. The measured parameters of grape quality of ‘Merlot’ and ‘Vranac’ were not influenced significantly by crop load levels. V2, compared to the V1, showed the potential for increasing grape yield only for Merlot variety under experimental conditions. The results of this study also showed a positive correlation between total phenolics/flavonoids and total antioxidant capacity of grape berries in both varieties, regardless of crop loads applied.